The Effect of Effleurage Massage using Canola Oil on the Risk of Pressure Ulcer in Stroke Patient - Rizaldi Nanda Wiguna; Afni Yan Syah; Rike Mah Tawar; Intan Dara Phonna; Sayidina Albani (Indonesian Journal of Global Health Research, 2025)
Stroke is a sudden disease that disrupts blood flow in the body, a brain condition causing disability, immobility, and prolonged paralysis, which reduces blood supply to tissues, especially in patients with prominent bones, increasing the risk of pressure ulcers. This study aimed to identify the effect of effleurage massage using canola oil on the risk of pressure ulcers in stroke patients at Kesdam Iskandar Muda Hospital. The study employed a Quasi-Experimental design with a pretest and posttest approach. The sampling technique used was non-probability sampling, specifically convenience sampling, with a total of 30 participants. The instrument used was the Braden Scale. Data were analyzed using a paired t-test. The study showed that the risk of pressure ulcers in ischemic stroke patients before the intervention was as follows: severe risk (70.0%), mild risk (20%), moderate risk (6.67%), and very severe risk (3.33%). After the intervention, the risk distribution changed to mild risk (60%), severe risk (33.33%), moderate risk (3.33%), and very severe risk (3.33%). Statistical analysis revealed a p-value of 0.001 (<0.05), indicating that effleurage massage using canola oil significantly affects the risk of pressure ulcers in stroke patients. This study confirms that effleurage massage using canola oil has a significant effect on reducing the risk of pressure ulcers in stroke patients.